Validity and Reliability Tests of Instruments Measuring Pregnant Women’s Spiritual Needs - Wahyuni, Sri; Istikhomah, Henik; Murwati, Murwati; Sayuti, Nutrisia Aquariushinta (Jurnal Keperawatan Soedirman, 2025)
The validity and reliability test of the spiritual needs instrument for pregnant women has never been conducted, where spiritual needs are important to develop a coping mechanism for adaptation during pregnancy. The purpose of this study was to test the validity and reliability of the spiritual needs instrument for pregnant women. The validity test was conducted by distributing questionnaires to 35 pregnant women during August - September 2024. The spiritual needs instrument used is based on the Patients Spiritual Needs Assessment Scale using a 5-point Likert scale, namely very inappropriate (score 0), inappropriate, not sure, appropriate, and very appropriate (score 4). Pearson correlation test of 38 statements of Spiritual Instrument of Pregnant Women showed that there were 33 valid statements with r count ≥ 0.256 (r: -0.036-0.641) and 6 invalid statements with r count < 0.256 (r: - 0.036). The Cronbach Alpha value with the smallest Cronbach Alpha value if the item is deleted is 0.890 and the highest value is 0.908. This instrument can validate and measure spiritual needs accurately, so that midwives can provide midwifery care by utilizing spiritual potential to facilitate the spiritual adaptation of pregnant women which varies in each trimester